2009
DOI: 10.1126/science.1169218
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Cue for Protein Localization in a Bacterium

Abstract: Proteins in bacteria often deploy to particular places within the cell, but the cues for localization are frequently mysterious. We found that the peripheral membrane protein SpoVM recognizes a geometric cue in localizing to a particular membrane during sporulation in Bacillus subtilis. Sporulation involves an inner cell maturing into a spore and an outer cell nurturing the developing spore. SpoVM is produced in the outer cell where it embeds in the membrane that surrounds the inner cell but not in the cytopla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
188
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 188 publications
(193 citation statements)
references
References 18 publications
5
188
0
Order By: Relevance
“…However, the mechanisms by which landmark proteins initially achieve their own proper localization are frequently unclear. Previously, we proposed that during sporulation in B. subtilis, the slightly convex surface of the developing forespore provides a geometric cue for the initial localization of the shape-sensing amphipathic α-helical protein SpoVM (24). In this report, we describe a previously unidentified structure-motivated mechanism by which SpoVM discriminates between differently curved membrane surfaces.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…However, the mechanisms by which landmark proteins initially achieve their own proper localization are frequently unclear. Previously, we proposed that during sporulation in B. subtilis, the slightly convex surface of the developing forespore provides a geometric cue for the initial localization of the shape-sensing amphipathic α-helical protein SpoVM (24). In this report, we describe a previously unidentified structure-motivated mechanism by which SpoVM discriminates between differently curved membrane surfaces.…”
Section: Discussionmentioning
confidence: 79%
“…To determine the biochemical basis for the preferential adsorption of SpoVM onto slightly convex membrane surfaces, we first sought to generate a saturation-binding curve by incubating membrane surfaces of a given curvature with a range of concentrations of purified SpoVM-GFP. Previously, we demonstrated that purified SpoVM-GFP selectively bound to lipid vesicles similar in size to the forespore in a mixture of giant unilamellar vesicles of various sizes (24). In the current investigation, we eliminated limitations associated with giant unilamellar vesicles (variability in vesicle size and associated variability in membrane stiffness) by using SSLBs, in which a single phospholipid bilayer is assembled on the surface of silica beads of defined size (29,30).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Several observations suggest that cell curvature influences the distribution of cytoplasmic, amphiphilic proteins in bacteria. For example, in the rod-shaped bacterium B. subtilis, membrane curvature affects the localization of the sporulation factor protein SpoVM (via positive curvature) and multimers of the division protein DivIVA (via negative curvature) (13)(14)(15). The mismatch in length scales between a single molecule of DivIVA or SpoVM and the curvature of the membranes with which these proteins interact makes it unclear how individual proteins sense curvature.…”
mentioning
confidence: 99%
“…In contrast, the IMDs fall within the I-BAR subfamily of BAR domains and cause convex deformation of membranes, inducing membrane protrusions; members of this subfamily, including IRSp53, have been shown to be involved in filopodia formation. Although BAR domain proteins have not been identified in bacteria, a recent report (9) describes the ability of the Bacillus subtilis peripheral membrane protein SpoVM to recognize the outer surface of spherical bacterial membranes or vesicles; although the structure of SpoVM has not yet been determined, the protein differs from known BAR domain proteins in that it forms an amphipathic ␣-helix with the hydrophobic face buried in the membrane and the positively-charged surface exposed (10).…”
mentioning
confidence: 99%